Adoption trends of point of issue Verax PGD rapid test for bacterial screening of platelets between 2013 and 2018 among hospitals supplied by the American Red Cross and impact on platelet availability. Issue 7 (19th May 2020) - Rios, Jorge; Westra, James; Dy, Beth; Young, Pampee P.
Abstract : BACKGROUND: Point‐of‐issue tests, such as the Verax Pan Genera Detection (PGD) test, can be used to mitigate the occurrence of septic reactions. Little is known about how widespread the adoption of the PGD test is across US hospitals. STUDY DESIGN/METHODS: The Red Cross hemovigilance database was used to determine the numbers of PGD‐positive test results between 2013 and 2018. An examination of the impact of a reactive PGD test on product availability was performed for 2018. RESULTS: The number of reported cases doubled, rising from approximately 50 to 100 per year between 2013 and 2018. A total of 475 initially reactive PGD tests during the entire study period were reported, and 7 (1.5%) of these were determined to be true positives. Hospitals surveyed reported testing platelet units once, with no repeat testing if the unit was PGD reactive. Evaluation of the reported PGD reactive cases for apheresis platelets for 2018 (n = 93) resulted in an estimated cost to the blood center of $87, 000, which included the labor and material costs of working up the cases and the estimated value of the lost 64 units and co‐components. In addition, there was a loss of the opportunity to collect over 85 apheresis platelets during the time the implicated donor was temporarily deferred. CONCLUSIONS: The number of hospital reports of reactive PGD tests has shown modest growth in the past 5 years. The number of initially reactive PGD tests that were confirmed was minimal. Blood centers can incur cost and platelet inventory loss from initially false‐positive test results.